P66 Cross-sectional and longitudinal associations between alcohol licensing policies, outlet density and deprivation and population health and crime in England. (13th September 2016) - de Vocht, F; Heron, J; Mooney, J; Angus, C; Lock, K; Egan, M; Campbell, R; Brennan, A; Hickman, M
Abstract : Background: An important policy area to address the cumulative effects of the use of alcohol on communities is that of regulating the physical availability of alcohol and modifying the commercial drinking environment. Such policies may not be directly aimed at public health, but primarily aim to target crime and anti-social behaviour, and can have a downstream effect on population health as well. Here, we analysed the effect of the intensity of local area alcohol licensing policy and enforcement on the cumulative impact on crimes and population health. Methods: Home Office Alcohol and Late Night Refreshment Licensing data was linked to local-area alcohol-related hospital admission from the Local Alcohol Profiles for England, population size and deprivation. Cumulative policy and enforcement intensity (hereforth 'intensity') was coded as 'passive', medium or high based on presence of cumulative impact zones and/or successfully challenged licenses applications. Temporal trends in directly age-standardised rates alcohol-related hospital admissions and rates of reported (alcohol-related) violent crimes, sex crimes, public order offences, and other crimes for 2009–15 were analysed using mixed-effects log-rate models adjusted for seasonality, population size, deprivation, and alcohol outlet density. Results: Crimes and alcohol-related hospital admissions were moderately to strongly correlated at the local level, illustrating the potential cumulative burden on certain areas partly attributable to alcohol use. Cross-sectionally, alcohol-related population harms and alcohol outlet density were higher in more deprived areas, but these were also the areas with the highest policy and enforcement 'intensity'; indicating that introduction of licensing policies was not done randomly but targets specific, and on average the correct, areas. Longitudinally, 'exposure'-response associations were observed, with an additional average decrease in alcohol-related hospital admission rates in the areas with the highest 'intensity' of 2% (95% CI: −3 to −2%) annually ( P = 0.006). Patterns for crime rates were more complex, but indicate that in 2009–2012 stronger reductions were similarly observed in more 'intense areas'. This pattern was not observed for 'financial fraud', which we characterised as not related to alcohol consumption. Post-2012 however, crime rates increased again, but faster in more 'intense' areas (although changes in reporting requires cautious interpretation). Conclusion: These results add to the available evidence about the potential benefits of alcohol licensing policies and enforcement in England. Moreover, they indicate that alcohol licensing policies are part of a wider policy package aimed at tackling cumulative burdens of more general crimes and anti-social behaviour and which positively affects population health.